Flexible and transparent electrode based on silver nanowires and a urethane acrylate incorporating Diels–Alder adducts. (25th December 2015) - Kim, Youngmin; Lee, Da Hee; Kim, Dong-Hwan; Kim, Jong-Woong
Abstract: Networked structures of Ag nanowires (AgNWs) are promising candidates for producing a wide range of flexible electronic devices. Embedding AgNWs into the surface of a transparent polymer film is considered a powerful method for achieving high flexibility as well as competitive electrical/optical performance, but only if they can be suitably formed and retain their electrical characteristics when peeling the film from the substrate. Here, we synthesized a new transparent polymer by mixing a photoreactive Diels–Alder (DA) adduct with a UV-curable urethane acrylate. An interesting feature of this polymer is that the retro-DA reaction that occurs upon heating enables a smooth release of the cured polymer from the glass support, even by a manual peeling-off procedure. A comparison of the sheet resistance of the electrodes before and after peeling revealed an increase of less than 10%. The fabricated electrode was highly flexible and showed improved surface roughness. Furthermore, a satisfactory portion of the AgNWs remained exposed to air, which is optimal for their use in the fabrication of thin film devices. Graphical abstract: Highlights: A photoreactive Diels–Alder adduct and UV-curable urethane acrylate were polymerized. Silver nanowires (AgNWs) were embedded in the surface of the synthesized polymer film. By applying heat to the cured polymer, a retro-DA reaction enabled the smooth release of the film. The sheet resistance of the electrode increased by less than 10% after peeling from supporting glass.